SURVAI IMPLEMENTASI AKTIVITAS MUTU UNTUK PENINGKATAN DAYA SAING PRODUK KERAJINAN GERABAH DI BANTUL - Wirjono, Endang Raino; Raharjono, Agus Budi (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2017)
This study aims to survays the implementation of quality related activities that have been done in the pottery industry center. The intense competition in the business world, coupled with external demands, presents its own challenges for MSMEs engaged in pottery in Kasongan. Therefore, this research will identify the quality related activities that have been done by the UMKM. The identification and analysis of such quality related activities will be used to find relevant advisory models and policy recommendations for developing the quality of products produced by UMKM Kasongan. Quality activity is an activity that arises because there may or may not be a poor quality product. Quality activity is divided into 4 components: prevention activities, appraisal activities, internal failure events, and external failure events. This research was conducted on 45 micro and small companies in Kasongan Craft located in Kajen pedukuhan, Bangunjiwo village, Kasihan district, Bantul, Yogyakarta Special Region. Data collection was done by distributing questionnaires, interviews and observation directly.Keywords: Prevention Activity, Assessment Activity, Internal Failure Activity, External Failure Activities, Pottery